Experimental study on passively-mode locked fiber lasers - Koh, Mabel Tengji (2017)
This report includes the principles of laser, theories of fiber optics, rare earth doped fiber laser and mode locking so that they may be understood by anyone. An experimental study of a thulium doped fiber laser was used as the gain medium of the laser, it was then mode locked by using the Nonlinear Polarization Rotation (NPR) technique. This technique had been successfully used to obtain short pulse generation in the thulium doped fiber laser.